Physical properties of a Eu 3+ -doped Zn 2 SiO 4 phosphor ceramic material with enhanced thermal sensitivity at low temperatures - Bessadok, M. N.; Bouri, A.; Ananias, D.; Mrabet, S.; Vázquez-Vázquez, C.; El Mir, L. (RSC advances, 2024)
In the present study, a SiO 2 /Zn 2 SiO 4 :Eu glass–ceramic composite was synthesized by a homemade modified sol–gel method. Structural, morphological, and optical properties were investigated. Structural and morphological analysis proves the existence of silica and zinc silicate phases with the latter surrounded and shielded by the silica matrix. Optical–vibrational analysis shows the fingerprint peaks of a Zn 2 SiO 4 material, confirming the good establishment of the phase. Photoluminescence plots reveal the presence of strong Eu 3+ ion emission lines that come from radiative recombination from 5 D 0 to 7 F J ( J = 0–4) inner states. The curves prove, as well, the appearance of weak wide blue (450 nm) and green (530 nm) bands related, respectively, to oxygen deficiency and zinc vacancy emission centers related to silica/zinc silicate intrinsic defects. The latter are taken as a starting point to investigate the thermometry properties of the sample by combining them with the europium principal emission lines ( 7 F 1,2 ) to get a maximum relative sensitivity of 2.36% K −1 at the [12–140 K] temperature range. The findings are promising and show, for the first time, the thermometry study of Eu-doped zinc silicate at below room temperature range.